Bhartiya swatantra andolan ka itihas - Tarachand (New Delhi Publication Division, Ministry of Information & Broadcasting, GOI, 2017)
History-India-Freedom Struggle
Itihas-Bhartiya Swatantra Andolan
In 4 volume